High technology spin-offs from government R&D laboratories and research universities - Carayannis, Elias G.; Rogers, Everett M.; Kurihara, Kazuo; Allbritton, Marcel M.
Following a study of seven spin-off organizations in New Mexico and Japan, the authors suggest a more complex definition of 'spin-off' expanding somewhat on the current definition which centres on technological innovation and entrepreneurs.
The present paper examines the high-tech spin-off process through which a new company is formed from a parent organization. Here we investigate spin-offs from three U.S. Federal R&D laboratories in New Mexico, and from Japanese government laboratories and universities. The spin-off process is one important means of transferring and commercializing technological innovations. Our study of seven spin-off companies leads us to suggest a more complex definition than the conventional definition, which centers on (1) the technological innovation, and (2) the entrepreneurs who found the spin-off.
Keywords: Technology spin-offs.